2014
DOI: 10.1371/journal.pone.0084985
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Developing Major Adverse Cardiovascular Events in Stented Chinese Patients Treated with Dual Antiplatelet Therapy after Concomitant Use of the Proton Pump Inhibitor

Abstract: BackgroundSome clinical studies have demonstrated that the proton pump inhibitor (PPI) could decrease clopidogrel platelet response and increase major adverse cardiovascular events (MACE) in white or black subjects. However, that remains to be determined in Chinese patients. In this study, we sought to determine whether there could be an increased risk for developing MACE after concomitant use of dual antiplatelet therapy (DAT) and a PPI in Chinese patients treated with percutaneous coronary intervention (PCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 29 publications
2
38
0
1
Order By: Relevance
“…A retrospective cohort study from China, including about 6200 patients who received aspirin plus clopidogrel with a PPI, reported that PPI users had a 3% increase in MACE compared with non-users. 60 Another retrospective cohort from Italy reported an alarming 12% increase in MACE in patients receiving a PPI in conjunction with clopidogrel. 61 …”
Section: Consensus Statementsmentioning
confidence: 99%
“…A retrospective cohort study from China, including about 6200 patients who received aspirin plus clopidogrel with a PPI, reported that PPI users had a 3% increase in MACE compared with non-users. 60 Another retrospective cohort from Italy reported an alarming 12% increase in MACE in patients receiving a PPI in conjunction with clopidogrel. 61 …”
Section: Consensus Statementsmentioning
confidence: 99%
“…Observational studies have also reported significant interaction between clopidogrel and PPIs, leading to an increased risk of adverse cardiovascular outcomes . Recent retrospective studies also reported that PPI users had a significantly higher incidence of MACE or stent thrombosis events than non‐users . Conversely, other studies, including four randomized clinical trials and two systematic reviews, have showed no clinically significant drug interaction between PPIs and clopidogrel.…”
Section: Proton Pump Inhibitors Impair the Antiplatelet Activity Of Cmentioning
confidence: 99%
“…10,23,[28][29][30] Recent retrospective studies also reported that PPI users had a significantly higher incidence of MACE or stent thrombosis events than non-users. 31,32 Conversely, other studies, including four randomized clinical trials [33][34][35][36] and two systematic reviews, 37,38 have showed no clinically significant drug interaction between PPIs and clopidogrel. However, the results from one randomized controlled trial, examining the potential interaction between clopidogrel and the PPI omeprazole with cardiovascular (CV) events as the outcome, could not exclude a clinically important increase in CV risk of up to 44%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 ] Proton pump inhibitors (PPIs) are usually prescribed for patients on DAPT to attenuate the side effects, [ 5 7 ] but there are concerns of adverse interactions of antiplatelet drugs and PPIs. [ 8 , 9 ] Current guidelines do not recommend the routine use of PPIs by patients with a low risk of GI bleeding [ 1 ] and advise that combination therapy with DAPT and PPIs has the potential of adverse drug interactions. [ 7 9 ]…”
Section: Introductionmentioning
confidence: 99%